2018
DOI: 10.1002/aoc.4566
|View full text |Cite
|
Sign up to set email alerts
|

Highly resilient polyethylene elastomers prepared using α‐diimine nickel catalyst with highly conjugated backbone

Abstract: An α-diimine nickel catalyst (Cat-1) with highly conjugated acenaphthylene backbone was synthesized and used in ethylene polymerization. Compared with typical Brookhart catalyst B-Cat, Cat-1 could produce polyethylene with both higher molecular weight (up to 5.1 × 10 5 g mol −1 ) and branching density (up to 135 branches per 1000 carbons) in good polymerization activity. The polyethylene prepared using Cat-1 with higher molecular weight and branching density possessed exceptional mechanical properties (ultimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…At such high temperatures, it is of great challenge for the catalysts to maintain high activity while producing polymers having high molecular weights. [5,[33][34][35] It has been found that the CGC possesses a high copolymerization activity for α-olefin at high temperatures. [36] During the olefin copolymerization catalyzed by the methyl silicon-bridged CGC-Ti (A in Figure 4), the chain transfer to monomer results in the formation of vinyl-terminated macromonomers that can be readily inserted into the propagating chains in situ.…”
Section: Random Copolymerization Of Ethylene and α-Olefinmentioning
confidence: 99%
See 1 more Smart Citation
“…At such high temperatures, it is of great challenge for the catalysts to maintain high activity while producing polymers having high molecular weights. [5,[33][34][35] It has been found that the CGC possesses a high copolymerization activity for α-olefin at high temperatures. [36] During the olefin copolymerization catalyzed by the methyl silicon-bridged CGC-Ti (A in Figure 4), the chain transfer to monomer results in the formation of vinyl-terminated macromonomers that can be readily inserted into the propagating chains in situ.…”
Section: Random Copolymerization Of Ethylene and α-Olefinmentioning
confidence: 99%
“…The type of branch structure is determined by the ratio of the chain walking rate to the chain propagation rate. [34,[55][56][57][58][59][60] It is worthy of note that such a ratio could be tuned by the catalyst structure and reaction conditions, such as pressure. Chen et al [55] synthesized α-diimine nickel catalysts with -Ph substituent (Ni-Ph), which catalyzed the ethylene polymerization to produce POEs (C in Figure 3).…”
Section: Chain Walking Polymerizationmentioning
confidence: 99%
“…The branch DOI: 10.1002/marc.202300221 density of the product can be regulated by the modification of the catalyst structure and the adjustment of polymerization conditions, which has good application potential. [11][12][13][14][15][16] Over the past three decades, the modification of the catalyst structure has been the main research direction, such as the change in the N-aryl structure [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] or the backbone structure, [34][35][36][37][38][39][40][41][42][43][44] even the introduction of strong combination strategy. [45][46][47][48][49] Improving the catalyst thermal stability is what researchers are passionate about, which is related to the industrial application of catalysts, but there are few related pieces of research about the inactivation mechanism.…”
Section: Introductionmentioning
confidence: 99%